Huaier suppresses pancreatic cancer progression via activating cell autophagy induced ferroptosis - Zhu, Zeen; Wang, Xueni; Zhang, Wunai; Gong, Mengyuan; Zhang, Simei; Yang, Bao; Qu, Bolun; Wu, Zheng; Ma, Qingyong; Wang, Zheng; Qian, Weikun (Frontiers in Oncology, 2022)
Purpose: The anti-tumour effect of Huaier has been demonstrated in a variety of tumours. Ferroptosis is a newly identified type of programmed cell death accompanied by the accumulation of reactive oxygen species (ROS) and iron in cells and plays a key role in the therapeutic process against malignant tumours. We aimed to explore the potential therapeutic role of Huaier in pancreatic cancer and uncover the relationship between Huaier and ferroptosis. Methods: CCK8 and colony formation assays were used to determine the proliferation of pancreatic cancer cells (PCs). The levels of cellular ROS were analysed by a fluorescence probe, and the accumulation of cellular iron was showed by Prussian blue staining. The autophagosomes and mitochondrial morphology were characterized by transmission electron microscopy (TEM). The levels of intracellular glutathione (GSH) and lipid peroxidation were measured by the corresponding kits. Results: The growth inhibitory effect of Huaier on PCs was concentration- and time-dependent, but this effect was significantly attenuated by ferroptosis inhibitors. In addition, Huaier effectively inhibited the GSH–GPX4 antioxidation system and resulted in the massive accumulation of ROS in PCs As shown by TEM, Huaier-treated PCs exhibited a decrease in mitochondrial cristae and a smaller mitochondrion, accompanied by an increase in autophagosomes. Indeed, we found that autophagy can induce ferroptosis in PCs and that Huaier-induced ferroptosis can be suppressed by the autophagosome inhibitor, Wortmannin. Conclusion: Huaier can activate ferroptosis by inducing autophagy in PCs.